Історико-архітектурна характеристика міста Сколе до початку промислової революції - Тарас, В. Я.; Taras, V. (Видавництво Львівської політехніки, 2019)
Проаналізовано процес виникнення та становлення міста Сколе. Визначено рівень впливу власників міста Сколе на планувальну структуру, оборонну, торговельну, ремісничу, адміністративну, репрезентативну, духовно-релігійну, культурно-освітню функції. Розглянуто колонізаційні процеси, які відбувались на Сколівщині.

The first written mention of Skole - a small Boyk settlement in the Carpathians dates from March 5, 1397. Nearly 1660, near the settlement of Skole, Prince Alexander Yanush Zaslavskyj lays a town and calls it his honor - Alexandria. The town is stretched in the basin of a lens shaped length of 3.5 km, a width of 1.5 km. The plan of the city had a geometric shape, close to the square, with a rectangular-mesh architectural-planning scheme. The center of planning composition and communication node of the city of Skole was a square market square, in the middle of which was the Town Hall. In addition to the streets that led to the square at the corners of pre-market districts, it crossed the main street from east to west, along which was the main Carpathian trade route. He divided the township's territory into two parts: the nobility, where there was a princely castle and wooden houses of the procession gentry; and boyish, or rustic. In Skole there was a large Jewish community with a synagogue and a cemetery. In Skole in the second half of the XVII c. there were at least two Christian churches. Prince Alexander Yanush Zaslavskyj builds a wooden castle, as far away as possible from the devastating water of the River Opp. The castle is located on the outskirts of the city, in the northwestern part. The castle was surrounded by a square, in the plan, of a wall constructed of stone logs. A wooden tower with loopholes rose above the gate. On the perimeter of the palace houses and household buildings. In the middle of the Dytyntsi the owner's house is located, surrounded by sunbathing. It was similar to other mountain villages, only higher and wider in size. The following owners of Helena Lyubomyrskaya and Theofil Lyubomirskaya contributed to the development of trade. Wine trade was introduced. In Skole, if necessary, open a customs warehouse. In 1778 the Skolivskyj key passed to Isabella Czartoryskaya. For the revival of the economy of Skolivshchyna Izabella Lyubomyrska in the last quarter of the XVIII c. invites German colonists. It was the beginning of a long period of gradual German colonization of the land, which took place in several stages. German colonists (bakers, locksmiths, watchmakers, shoemakers) settled mainly in Skole and were engaged in crafting. Princess Isabella Lyubomirskaya opened the iron and glass guta. June 10, 1772 in Skole entered the Austrian troops. At the beginning of the XIX c. with the support of Franz Joseph I, began the next stage of the massive colonization of the Boykivshchyna by German artisans. They founded several colonies where they settled compactly: Felicenthal (Dolinovka village), Karsdorf (now Climate village) and Annaberg (now the village of Nagirne). Many German families settled down in Skole itself. German colonization contributed to the development of the province's industry. Its influence is still noticeable in construction, everyday life, local dialect, farm management. In 1859 the great-grandson Countess Count Stanislav Pototsky sold Skolvyi land together with Tukhlovs'kyi Count E. Kinski, who changed the mining activities to the forestry industry. Graf Y. Kinsky introduces the achievement of an industrial revolution in Skole and its surroundings, contributing to the emergence of a market economy in the second half of the XIX th and early XX th c.
Historical and architectural characteristics of the city Skole before the beginning of industrial revolution
Keywords: Бойківщина; Сколе; планувальна структура; оборонна; торговельна; реміснича; адміністративна; духовно-релігійна функції; Boijkivshchyna; Skole; town planning; architecture; self-government; settlement; culture; education; 711.424